The Influence of Digital Communication on Customer Satisfaction in the Hotel Sector: Study Literature Review - Asthiti, Ayu Ngurah Quintina; Suryadharma, Mochamad; Lubis, Syahrial Rachim (Yayasan Ilomata, 2024)
This study aims to analyze the effect of digital communication on customer satisfaction within the hospitality sector. The research employs a qualitative methodology with a literature study approach, utilizing secondary data from articles, journals, and books relevant to digital communication and customer satisfaction in hospitality. NVivo software is used as the analytical tool to systematically organize and analyze the collected data. The findings indicate that digital communication significantly improves customer satisfaction by enhancing convenience, personalization, real-time communication, and service delivery. Social media, mobile applications, and email communication are highlighted as key platforms that facilitate these improvements. However, challenges such as data privacy, security, and integration of digital tools must be addressed to maximize the benefits. The study underscores the importance of developing comprehensive digital communication strategies to meet and exceed customer expectations in the hospitality sector.